Comprehensive Economic Strategies for Advancing Development in the Digital Economy - Tripathy, Pradeeth; Tara, Kiran; Niya, Aarush (Journal Development Manecos, 2024)
This work aims at identifying the key elements that underpin the establishment of digital economy with emphasis on innovations, digital infrastructure, policies and education. Employing an exploratory, non-experimental, quantitative research design, survey data were obtained from 500 participants using a standardised and psychometrically sound questionnaire. The above multiple regressions confirmed that innovation leads to greater degrees of digital economic growth than the components of digital infrastructure, digitized regulations, and educational enablers. In doing so the results highlight the significance of these elements in the continuation of economic development in the post-industrial age. The study also validity and reliability of the survey instrument is confirmed through a pilot study with Cronbach’s alpha is 0. 78 and they are also all above the cutoff level of successful factor analysis. An analysis of variance indicated that there are no significant intersectorial and demographic differences in perceptions of effectiveness of digital strategies. Finally, this study contributes to the development of literature in the area of digital economics by establishing the importance of each of the quantitative predictors of Internet use and specifically identifying digital economic growth’s major factors. The results also presented relevant information for policymakers, educators, and businesses who would like to develop and improve the digital economic development sources and future. Future research should also try and establish these relationships within different settings and different populations in order to elaborate on this research.